Islamic Financial Technology and its impact on the development of Malaysian investment sukuk: the experience of the Digital Sukuk Prihatin - lazreg, fatima; nemer, Rabiha (Journal of Research in Finance and Accounting, 2023)
The Islamic financial technology is one of the most important contemporary topics in the world and the Arab world, this study aimed to review and stand on the latest developments in the application of Islamic financial technology and its most important uses, achievements and repercussions on individuals and companies. The descriptive analytical approach has been relied upon to describe the various aspects of the subject and clarify the contributions of Islamic financial technology in the development of new services and products using technology algorithms and innovations. This is proven by the Malaysian experience, which created a favorable infrastructure and thus achieved the Asian tiger and developed the sukuk sector through the so-called digital sukuk, aiming to raise its economic efficiency and revive the economy after the Covid-19 crisis and make it a more competitive tool.